2005
DOI: 10.1007/s00330-005-2716-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right ventricular volume and mass using retrospective ECG-gated cardiac multidetector computed tomography: comparison with first-pass radionuclide angiography

Abstract: The purposes of this study were to evaluate the right ventricular (RV) volume and mass using cardiac multidetector computed tomography (MDCT) and to compare the cardiac MDCT results with those from first-pass radionuclide angiography (FPRA). Twenty patients were evaluated for the RV end-diastolic volume (RVEDV), the RV end-systolic volume (RVESV), the RV ejection fraction (RVEF), and RV mass using cardiac MDCT with a two-phase reconstruction method based on ECG. The end-diastolic phase was reconstructed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…In addition to preoperative staging of the underlying respiratory disease, a given data set not only can participate in the screening for coronary artery disease, as recently reported for respiratory patients [19] as well as for the rapid triage of patients presenting to emergency centers with chest pain [16,33], but is also able to provide cardiac functional information in candidates for chest surgery. Although this latter aspect was not investigated in our protocol, several recent studies have demonstrated that 16-and 64-slice MSCTs were accurate and reliable non-invasive techniques for evaluating right and left cardiac function [18,20,[34][35][36], providing vital information for the management of patients with a wide variety of acute or chronic respiratory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to preoperative staging of the underlying respiratory disease, a given data set not only can participate in the screening for coronary artery disease, as recently reported for respiratory patients [19] as well as for the rapid triage of patients presenting to emergency centers with chest pain [16,33], but is also able to provide cardiac functional information in candidates for chest surgery. Although this latter aspect was not investigated in our protocol, several recent studies have demonstrated that 16-and 64-slice MSCTs were accurate and reliable non-invasive techniques for evaluating right and left cardiac function [18,20,[34][35][36], providing vital information for the management of patients with a wide variety of acute or chronic respiratory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Three approaches were proposed, one investigating cardiac global function during a whole-chest multislice CT acquisition with a 16×1.5-mm collimation to ensure an acceptable breath-hold duration [6], one investigating a two-phase protocol to scan both the entire thorax and cardiac cavities with the highest spatial resolution [7], while the third one evaluated a dedicated cardiac MDCT protocol to assess right ventricular function and mass [8]. Comparing ECG-gated 16-slice multidetector row CT (MDCT) with equilibrium radionuclide ventriculography, these preliminary studies demonstrated the feasibility of such an approach in limited populations of hemodynamically stable patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several authors have described techniques to measure cardiac output using cine computed tomography [1][2][3][4][5][6][7]. Unlike our method, these techniques are complex and based on mathematical modeling.…”
Section: Discussionmentioning
confidence: 81%
“…Theoretically, different techniques can be used to estimate cardiac function with CT. First, myocardial contours can be determined at end-diastole and endsystole, and functional parameters such as ejection fraction, end diastolic volume and cardiac output can be calculated [1][2][3][4]. However, this approach is not commonly used because of the need for ECG triggering and postprocessing.…”
Section: Introductionmentioning
confidence: 99%